Peter Fritz and Nicholas K. Jones (eds.), Higher-Order Metaphysics - Felipe Carrasco Figueroa (Crítica)
Peter Fritz and Nicholas K. Jones (eds.), Higher-Order Metaphysics, Oxford University Press, 2024, vii + 547pp., ISBN 978–0–19–289488–5